Cyberbullying in school: A literature review - Oliveira, Paulo (2019)
This work aims to perform a systematic review of literature on cyberbullying in the Scielo – Brazil database to verify the amount of studies on this theme in this database that is a reference in relation to Brazilian scientific production. For the accomplishment of this search the Scielo – Brazil database was used, from the descriptors cyberbullying and school in the Portuguese, English and Spanish languages. The sample consisted of four studies, among the twenty found in the search. Where are found eight articles in Portuguese, nine in English and three in Spanish related to the descriptors of the research. However, only four of these studies met the criteria of selection of this systematic literature review, two in Portuguese, one in English and one in Spanish. It was verified that all the investigations detected the presence of cyberbullying in the relations between the students, as well as there was a variation between 1.9% and 11.4% for the rate of victimization by cyberbullying and a variance between 3.9% and 12.5% for the rate of aggression by cyberbullying. With this investigation we conclude that cyberbullying is still little investigated in the Brazilian population and that new research is needed to deepen the knowledge about the subject, which is of great importance, since this type of violence can be seen as a public health problem, and should receive attention from public policy makers.